High school background and academic performance - Gerardo P. Sicat; Marian Panganiban (University of the Philippines, School of Economics (UPSE), 2009)
Human capital formation during youth, aside from the individual qualities of the student, is dependent in part on the quality of the schooling background. The determinants of academic performance of students (measured by their grade in the introductory economics course in the University of the Philippines) are studied taking into account the student's pre-collegiate endowment of knowledge and various factors associated with the high school of graduation. The study affirms that individual student ability is the main building block of academic performance in the university. The high school of graduation is a secondary factor if at all important. Talent distribution in the country is widely distributed across the country and those who get admitted into the university are filtered through a stringent entrance examination score that has major components in science, mathematics, reading and language comprehension come from the small group of bright outliers from this population of high school graduates. There is a strong indirect link to the quality of the high school background. When the entrance test score is used as the dependent variable, the high school background plays an important role. The average performance of high schools from the Metro Manila regions is better than those from other regions of the country. In the same manner high schools from well-funded first class cities perform very well compared to those from less financially endowed cities. These findings indicate that the quality of funding and the level of development of the community in which the high school is located are contributory factors to the student's performance when they seek admission into the university.
Keywords: 330; Human capital formation; collegiate education; high school education; introductory Economics; economic development; Allgemeinbildende Schule; Humankapital; Studierende; Wirtschaftsstudium; Philippinen